Synthesis, Characterization, and Antimicrobial Potentials of Some Flavonoid-Metal Complexes from Chromolaena Odorata - Bamigboye, Oluwaseyi M.; Ejidike, Ikechukwu P.; Lawal, Misitura (Iraqi Journal of Science, 2020)
Flavonoid-metal complexes from the medicinal plant, Chromolaena Odorata were synthesized in this study using a standard method. Flavonoid extracts complexes, namely Mn-flavonoid complex, Co-flavonoid complex, Zn-flavonoid complex, and Cd-flavonoid complex were characterized using Fourier-Transform Infrared spectroscopy technique (FT-IR). Based on IR data, it was observed that the complexes shifted to lower frequencieswhen compared with the extract, indicating the interaction of the C=O and O-H groups during the complex formation. It was observed that the complexes were synthesized at a certain condition, which is acidic,with pH values ranging from 2.11 to 3.68. The conductance values (Î›m) of the complexes were found to be in the range of 7-15 Î©âˆ’1 cm2 molâˆ’1, which indicates that the complexes are non-electrolytes. The synthesized flavonoid-metal complexes and the extract were assayed for antibacterial activity against several pathogenic bacteria (Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, Pseudomonas aeruginosa) and fungi (Aspergillus niger, Blastomyces dermatitidis, Candida albicans, Cryptococcus gattii) by measuring the zone of inhibition. The complexes were active and highly antibacterial to all organisms when compared with extract.